2012
DOI: 10.1016/j.adiac.2011.12.001
|View full text |Cite
|
Sign up to set email alerts
|

The extent of corporate governance disclosure and its determinants in a developing market: The case of Egypt

Abstract: The aim of this paper is to assess the extent of corporate governance voluntary disclosure and the impact of a comprehensive set of corporate governance attributes (board composition, board size, CEO duality, director ownership, block-holder ownership and the existence of audit committee) on the extent of corporate governance voluntary disclosure in Egypt. The measurement of disclosure is based on published data created from a checklist developed by the United Nations, which was gathered from a manual review o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

66
357
5
17

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 267 publications
(445 citation statements)
references
References 55 publications
66
357
5
17
Order By: Relevance
“…This proposition is explained in terms of positive accounting theory where modern companies are characterized by a separation of ownership and control. This arrangement for corporate control generates agency costs resulting from the conflicting interests between (i) management and owners, and (ii) across different classes of owners (Al-Moataz and Hussainey, 2010;Samaha et al, 2012;Klai and Omr, 2011;Ho et al, 2013). In other words, the greater the percentage of stocks owned by top managers, the more likely it is that they make decisions consistent with maximizing a company's wealth and providing transparent financial statements in order to optimise the current share price (Mak and Li, 2001).…”
Section: Ownership Structurementioning
confidence: 99%
See 2 more Smart Citations
“…This proposition is explained in terms of positive accounting theory where modern companies are characterized by a separation of ownership and control. This arrangement for corporate control generates agency costs resulting from the conflicting interests between (i) management and owners, and (ii) across different classes of owners (Al-Moataz and Hussainey, 2010;Samaha et al, 2012;Klai and Omr, 2011;Ho et al, 2013). In other words, the greater the percentage of stocks owned by top managers, the more likely it is that they make decisions consistent with maximizing a company's wealth and providing transparent financial statements in order to optimise the current share price (Mak and Li, 2001).…”
Section: Ownership Structurementioning
confidence: 99%
“…In particular, boards with a higher proportion of outside or independent directors will increase the monitoring of management because they are not affiliated to any internal parties from the company (Weir and Laing, 2003;Chau and Leung, 2006;Klai and Omr, 2011;Ho et al, 2013). Prior studies have also found that the presence of independent directors on boards may improve the quality of financial statements and corporate disclosures (Chen and Jaggi, 2000;Xie et al, 2001;Cheng and Courtenay, 2004;(Samaha et al, 2012;Al-Moataz and Hussainey, 2010;. For example, Mak and Li (2001) examined the determinants and interrelationships among corporate ownership characteristics and boards of directors using a sample of Singaporean listed firms.…”
Section: H3: Sector Membership Explains Fi Disclosures Corporate Govementioning
confidence: 99%
See 1 more Smart Citation
“…Generally, and notwithstanding the increasing number of CG Codes in developing countries, such as Saudi Arabia (Aguilera & Cuervo-Cazurra, 2009;Samaha et al, 2012), existing studies investigating the effectiveness of voluntary CG Codes in improving governance standards are disproportionately concentrated in a few developed countries (Bebenroth, 2005;Bozec & Bozec, 2007;Cromme, 2005;Hooghiemstra, 2012;Hussainey & Al-Najjar, 2012;Mallin & Ow-Yong, 2012;Pass, 2006;Pellens, Hillebrandt, & Ulmer, 2001;Salterio et al, 2013;Werder et al, 2005). It is contended, however, that in developing countries with different cultural, regulatory, CG, and institutional contexts, such as Saudi Arabia (Aguilera & Cuervo-Cazurra, 2009), voluntary compliance with CG Codes can be expected to vary from what has been found in developed countries.…”
mentioning
confidence: 99%
“…existing studies that empirically examine the different extent to which a firm's board and ownership mechanisms can serve as strong or weak antecedents of voluntary compliance and disclosure of good CG practices are generally rare (Bozec & Bozec, 2007;Collett & Hrasky, 2005;Hussainey & Al-Najjar, 2012;Mallin & Ow-Yong, 2012;Salterio et al, 2013), but particularly acute in developing countries (Ntim, Opong, Danbolt, & Thomas, 2012;Rouf, 2011;Samaha et al, 2012;Tsamenyi et al, 2007). This intuition is motivated by the fact that the capacity of CG codes to achieve good governance depends largely on the extent to which senior managers, owners, and companies are willing to engage in effective voluntary compliance and disclosure (Core, 2001;Ntim et al, 2013;Tariq & Abbas, 2013).…”
mentioning
confidence: 99%